Pengelolaan Supervisi Akademik Di SDN Kawatan No.19 UPTD Dikpora Kecamatan Serengan Kota Surakarta - Satiman, Satiman; , Dr. Wafrotur Rohmah, M.M (2017)
One of the main tasks and functions of the principal are as supervisor. So in managing education at school, the principal should manage academic supervision in a professional manner in order to develop academic supervision programs, and carrying out academic supervision, and conduct follow-up feedback and academic supervision. Because the Academic Supervision is a series of activities to help teachers develop the ability to manage the learning process for the achievement of learning objectives, while the principal is personally most responsible for the success of learning in schools. The purpose of this study is describe the program planning, implementation, feedback and follow-up Supervision of Academic State Primary School Kawatan 19 UPTD Surakarta.Sumber City District Dikpora Serengan research data consists of primary and secondary data sources. Sources of primary data in the form of text interviews obtained through interviews with informants sampled research, secondary data sources such as data provided obtained by researchers through reading, viewing, or listening. In collecting the data the researcher used observation, interviews and document analysis. Form of research is qualitative. Researchers analyzed the research with data collection, data reduction, data presentation, and data verification. This study shows that: a) If the Supervision of Academic planned schedule programmed, disseminated to the relevant parties, conducted by Supervisor competent, and using a valid instrument, and implemented collaborative participatory the academic supervision can be done well according to expectations b) If the Supervision of Academic implemented according to schedule, and Supervision of the implementation of learning process was assessed using valid instruments, and beginning with the monitoring and assessment administration lesson plan in preparation for the implementation of the learning process, the learning becomes quality, and c) If the Supervision of Academic done by conducting activity feedback and closely followed by discussion, exchange of ideas in a transparent and proportionate as well as a detailed description of the weaknesses or deficiencies in the lesson plan and the implementation of the learning process of learning the problems and constraints can be solved.